The Adaptation of Balinese Transmigrant Houses to the Nawa Sanga Concept - Wildha Mardhatillah; Mahyudi Usmar; Rizka Audina Papputungan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Balinese communities have spread across many regions of Indonesia, largely through government-organized transmigration programs intended to redistribute the high population density of Bali. This movement inevitably confronts Balinese migrants with the challenge of adapting their spatial and architectural values, particularly the Tri Hita Karana philosophy and the Nawa Sanga/Sanga Mandala spatial concept, which are closely tied to the traditional caste (catur wangsa) system, to new physical and socio-cultural environments outside Bali. This study aims to examine how Balinese transmigrant communities adapt their dwelling patterns to the Tri Hita Karana and Nawa Sanga concepts, taking the case of Kertoraharjo Village, Tomoni Timur Sub-district, East Luwu Regency, South Sulawesi, a settlement established through the 1972-1973 transmigration program. A descriptive qualitative method was employed, combining field observation and documentation of housing layout with a literature review, and situating the findings within recent studies on Balinese vernacular architecture and caste-based social structure. The results show that the spatial arrangement of Balinese transmigrant houses in Kertoraharjo does not fully follow the normative orientation, building placement, and zoning hierarchy prescribed by Tri Hita Karana and Nawa Sanga. This deviation is driven by the community's socio-economic condition and by a shift in the meaning of caste, in which social status is now determined more by individual achievement than by hereditary caste rank. Nevertheless, the community still regards the east as the most sacred direction, consistently placing the family shrine (pamerajan) at the easternmost part of the house. These findings indicate that Balinese architectural adaptation in transmigration areas reflects a negotiation between inherited cosmological order and new socio-economic realities.